2016
DOI: 10.1111/nph.13861
|View full text |Cite
|
Sign up to set email alerts
|

Identifying developmental phases in the Arabidopsis thaliana rosette using integrative segmentation models

Abstract: SummaryThe change in leaf size and shape during ontogeny associated with heteroblastic development is a composite trait for which extensive spatiotemporal data can be acquired using phenotyping platforms. However, only part of the information contained in such data is exploited, and developmental phases are usually defined using a selected organ trait. We here introduce new methods for identifying developmental phases in the Arabidopsis rosette using various traits and minimum a priori assumptions.A pipeline o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Various segmentation models have been previously applied to identify growth or developmental phases at different scales in plants (see e.g. Dambreville et al , 2015 ; Lièvre et al , 2016 ; Guédon et al , 2007 ). By identifying successive synchronous phases in flowering and by showing that the split into two perpetual flowering phases can be genetically explained, this study illustrates the relevance of statistical models for better characterizing dynamic developmental traits using longitudinal analyses of plant phenotyping data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various segmentation models have been previously applied to identify growth or developmental phases at different scales in plants (see e.g. Dambreville et al , 2015 ; Lièvre et al , 2016 ; Guédon et al , 2007 ). By identifying successive synchronous phases in flowering and by showing that the split into two perpetual flowering phases can be genetically explained, this study illustrates the relevance of statistical models for better characterizing dynamic developmental traits using longitudinal analyses of plant phenotyping data.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the dynamics of developmental traits have not explicitly been considered in genetic studies, whereas recent studies have shown an interest in longitudinal data analyses for deciphering such complex traits (see Dambreville et al (2015) concerning growth and developmental stages in mango growth units and Lièvre et al (2016) concerning developmental phases in Arabidospsis rosette). In this setting, the successive measurements of the developmental traits of interest are directly analysed with appropriated statistical models (see Diggle et al (2002) for a general introduction to longitudinal data analysis).…”
Section: Introductionmentioning
confidence: 99%
“…In order to capture such behavior, the proposed modeling framework can be extended directly by adding states in series for modeling successive growth phases for type A lateral roots. Such an extension of semi-Markov switching models with states in series was developed recently for modeling successive developmental phase in Arabidopsis rosettes by Lièvre et al (2016). We may expect a single state with decreasing growth rate following the current increasing growth rate state A or an intermediate roughly stationary growth state between the increasing and decreasing growth rate states.…”
Section: A New Experimental Design Is Required For Studying the Wholementioning
confidence: 99%
“…Most of these platforms generate traits that give a global view of the root architecture. By contrast, the development of individual roots during long periods of time is rarely studied, whereas temporal analyses are more developed for the aerial parts (Lièvre et al, 2016). These studies have been hampered by the difficulty of collecting individual root growth data.…”
mentioning
confidence: 99%
See 1 more Smart Citation